2007
DOI: 10.4315/0362-028x-70.11.2518
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation Kinetics and Factors of Variability in the Pulsed Light Treatment of Listeria innocua Cells

Abstract: Pulsed light (PL) treatment can effectively reduce microbial populations in clear substrates and on surfaces, but its effectiveness varies as a function of substrate or treatment-related factors. For PL to be successfully adopted by the food industry, all factors of influence, as well as the inactivation kinetics for the microorganisms of concern, must be elucidated. In this study, the inactivation kinetics of Listeria innocua and the effect of inoculum size on PL inactivation were investigated. Stainless stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 10 publications
6
31
0
Order By: Relevance
“…There is a need for optimizing the experimental parameters to achieve the target inactivation level for specific applications. Studies carried out by Uesugi et al (2007) demonstrated that PL is capable to deliver the same level of microbial reduction in clear liquids, regardless of the level of contamination. According to these authors, the Weibull model is adequate to accurately predict microbial inactivation in clear liquids, but it fails for products where the influence of various substrate properties on inactivation is significant.…”
Section: Liquid Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need for optimizing the experimental parameters to achieve the target inactivation level for specific applications. Studies carried out by Uesugi et al (2007) demonstrated that PL is capable to deliver the same level of microbial reduction in clear liquids, regardless of the level of contamination. According to these authors, the Weibull model is adequate to accurately predict microbial inactivation in clear liquids, but it fails for products where the influence of various substrate properties on inactivation is significant.…”
Section: Liquid Foodsmentioning
confidence: 99%
“…The efficiency of PL has shown to be influenced by inoculum size when the treatment is applied to surfaces (Uesugi et al 2007). Gómez-López et al (2005a) observed a strong decrease in inactivation efficiency when high counts of L. monocytogenes were reached on the surface of an agar medium.…”
Section: Process Critical Factorsmentioning
confidence: 99%
“…Since it has been previously determined that there is a linear relationship between fluence and the number of pulses (Uesugi et al, 2007), it was only necessary to measure the fluence per pulse at each (x, y, z) coordinate.…”
Section: Resultsmentioning
confidence: 99%
“…Sauer and Moraru found 5.76 log and 7.15 log reductions of E. coli O157:H7 in apple cider and apple juice, respectively, after PL treatments performed under turbulence, at fluence levels of up to 12 J/cm 2 (measured at the liquid surface) (Sauer and Moraru, 2009). Uesugi et al obtained a 6.04 log reduction of L. innocua in Butterfield phosphate buffer exposed to 13.3 J/cm 2 of PL (Uesugi et al, 2007). Krishnamurthy et al obtained a 7.5 log reduction of Staphylococcus aureus in phosphate buffer after a treatment dose of 84 J/cm 2 , and achieved up to 7 log reduction S. aureus in milk flowing at a rate of 20 mL/min at the same distance from the lamp (Krishnamurthy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Artíguez et al (2012) and Artíguez and de Marañón (2015) also reported a linear correlation between pulsed light inactivation rates and the transmittance of samples at different protein concentration. Furthermore, many studies found that Weibull model was accurate to explain the relationship between inactivation level and dose of the IPL (Bialka, Demirci, & Puri, 2008;Izquier & Gómez-López, 2011;Uesugi, Woodling, & Moraru, 2007). Further studies on extinction coefficient data for more diverse liquid samples and their inactivation level are needed to find best-fit regression kinetic model.…”
Section: Adequacy Of Inactivation Kinetic Equationmentioning
confidence: 99%